Private equity's unintended dark side: On the economic consequences of excessive delistings - Alexander Ljungsqvist; Lars Persson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2016)
Over the past two decades, private equity has contributed to a shrinking of the U.S. stock market. We develop a political economy model of private equity activity to study the wider economic consequences of this trend. We show that private and social incentives to delist firms from the stock market are not always aligned. Private equity firms could inadvertently impose an externality on the economy by reducing citizen-investors' exposure to corporate profits and thus undermining popular support for business-friendly policies. This can lead to long-term reductions in aggregate investment, productivity, and employment.
Keywords: G34; G24; P16; 330; Private equity; Political economy; Stock market; Delistings; Investment; Productivity; Private Equity; Börsengang; Aktienmarkt; Theorie; USA